An uncertainty metric to evaluate deformation vector fields for dose accumulation in radiotherapy. (April 2018) - Takemura, Akihiro; Nagano, Akira; Kojima, Hironori; Ikeda, Tomohiro; Yokoyama, Noriomi; Tsukamoto, Kosuke; Noto, Kimiya; Isomura, Naoki; Ueda, Shinichi; Kawashima, Hiroki
Abstract: Background and purpose: In adaptive radiotherapy, deformable image registration (DIR) is used to propagate delineations of tumors and organs into a new therapy plan and to calculate the accumulated total dose. Many DIR accuracy metrics have been proposed. An alternative proposed here could be a local uncertainty (LU) metric for DIR results. Materials and methods: The LU represented the uncertainty of each DIR position and was focused on deformation evaluation in uniformly-dense regions. Four cases demonstrated LU calculations: two head and neck cancer cases, a lung cancer case, and a prostate cancer case. Each underwent two CT examinations for radiotherapy planning. Results: LU maps were calculated from each DIR of the clinical cases. Reduced fat regions had LUs of 4.6 ± 0.9 mm, 4.8 ± 1.0 mm, and 4.5 ± 0.7 mm, while the shrunken left parotid gland had a LU of 4.1 ± 0.8 mm and the shrunken lung tumor had a LU of 3.7 ± 0.7 mm. The bowels in the pelvic region had a LU of 10.2 ± 3.7 mm. LU histograms for the cases were similar and 99% of the voxels had a LU < 3 mm. Conclusions: LU is a new uncertainty metric for DIR that was demonstrated for clinical cases. It had a tolerance of <3 mm.